The Effect of Golden Sea cucumber (Stichopus hermanii) and Hyperbaric Oxygen Therapy to The Expression of Osteoprotegerin in Diabetes Mellitus Induce by Porphyromonas gingivalis Bacteria - Luthvina Setiami Aziza; Kristanti Parisihni; Dian Mulawarmanti (Denta Journal Kedokteran Gigi, 2016)
Background: Diabetes mellitus (DM) with Periodontitis cause severe alveolar bone resorption. Osteoprotegerin prevent osteoclastogenesis process so that inhibited alveolar bone resorption. Stichopus hermanii powder and hyperbaric oxygen therapy (HBO) have content and good effects in wound healing. Purpose: The aim of this reseach was to analyze the effect of Stichopus hermanii powder and HBO therapy in the increasing of osteoprotegerin expression on DM with periodontitis. Materials and Methods: The research was an experimental laboratories post test only control group design. Twenty Wistar rats were divided into 5 groups. K0 was negative group while K1 was positive group K1-K4 groups were induced with 65mm/kg STZ single dose and 2ml bacterium P. gingivalis., K2 was treated with 3%golden sea cucumber powder in gel form. K3 was treated with OHB therapy 2.4 ATA for 7 days and K4 given a combination of both. Osteoprotegrin expression on osteoblast of alveolar mandible bone were examined by immunohistochemical staining. Data were analyzed by Kruskal-Wallis and Mann-Whitney test. Result: Kruskal-Wallis result showed significant differences from each treatment group (p <0.05). Mann-Whitney test showed the decreasion in the expression of osteoprotegerin between K1(2:50 ± 0.577) compare with K0 (p<0.05). Golden sea cucumber powder, HBO therapy and both combination had increased osteoprotegerin expression.significancy in K2(8.25 ± 1.258), K3 (5.75 ± 0.957) and K4(12.50 ± 2.082) (p<0,05). Conclusion: Stichopus hermanii powder 3% and 2.4 ATA OHB therapy for 7 days increased the expression osteoprotegrin on DM with periodontitis.